Slow cortical potentials in human aversive trace conditioning - Hellwig, Stefanie; Weisbrod, Matthias; Rentrop, Mirjam; Unger, Jörg; Walther, Stephan; Fiedler, Peter; Bender, Stephan (International journal of psychophysiology, 2008)
The aim of the present study was to better understand the cortical structures and neuronal processes involved in aversive differential trace conditioning in healthy subjects. According to previous findings in literature, we tested whether the stimulus preceding negativity (SPN) in an emotional trace-conditioning paradigm shows a frontocentral maximum reflecting affective anticipation, e.g. in the anterior cingulate, or a centroparietal maximum reflecting time estimation and sensory anticipation. Two distinct SPN intervals were analyzed, one during the presentation of the CS (comparable to delay conditioning) and another one after CS offset (trace conditioning). In the CS+ condition, where subjects anticipated the onset of an aversive electrical stimulus after CS+ offset, a significantly larger negativity than in the unpaired (CS−) condition was present. SPN revealed a sustained midcentral and posterior parietal negativity during both SPN intervals. Differences between the two analyzed SPN intervals pointed towards occipital activity being found in the first interval (delay), but not in the second (trace). Aversive conditioning paradigms with longer trace intervals seem to rely upon a similar activation pattern as cognitive stimulus anticipation.
Gesehen am 16.08.2021